2017
DOI: 10.1016/j.ejvs.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Year Results of Radiofrequency Ablation, Using VNUS Closure, for the Abolition of Truncal Venous Reflux in Patients with Varicose Veins

Abstract: RFA with VNUS Closure achieved excellent long-term technical success in treating venous reflux in truncal veins 15 years post-procedure, demonstrated by DUS. This bodes well for the increased use of EVTA in treating truncal vein reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…Fiveyear results from the prospective European multicenter cohort study RFA using the Venefit procedure showed GSV occlusion rate of 91.9% with 94.9% reflux free GSVs. 3 Recently, Whitely et al 42 reported an 88% success with no recurrence in the originally treated truncal veins, 15 years post RFA, as demonstrated by duplex. Other RFA systems are available (RFITT, Olympus, Germany and Venclose, USA), but the long-term efficacy is still less documented.…”
Section: Radiofrequency Ablationmentioning
confidence: 97%
“…Fiveyear results from the prospective European multicenter cohort study RFA using the Venefit procedure showed GSV occlusion rate of 91.9% with 94.9% reflux free GSVs. 3 Recently, Whitely et al 42 reported an 88% success with no recurrence in the originally treated truncal veins, 15 years post RFA, as demonstrated by duplex. Other RFA systems are available (RFITT, Olympus, Germany and Venclose, USA), but the long-term efficacy is still less documented.…”
Section: Radiofrequency Ablationmentioning
confidence: 97%
“…2,3 The safety and efficacy of endothermal ablation of truncal saphenous veins have been demonstrated 4 and recent unrivalled 15-year follow-up data using radiofrequency ablation (RFA) have shown excellent durable longterm technical success. 5 However, thermal techniques require the use of peri-venous tumescence to provide anaesthesia and to protect surrounding tissues from thermal injury. Tumescence administration, although generally well-tolerated, requires multiple injection sticks along the course of the saphenous vein, which can cause both intra-procedural and post-operative discomfort 6 as well as adverse events such as haematoma and ecchymosis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, RF procedure results seem to be stable for longer periods after the procedure. Proebstle et al reported a high occlusion rate of 91.9% of treated veins after five years of follow-up [43], while the study of the longest observation time after EVTA showed a rate of 88.1% of technical success 15 years after RF VNUS closure [44].…”
Section: Long-term Resultsmentioning
confidence: 99%